As atividades educativas profissionalizantes como possibilidades de aprendizagem nas perspectivas dos jovens na unidade Senador Raimundo Parente - Ferreira, Luana Thays Serzedelo (Brasil, 2025)
The right to education, including professional qualifications, is essential for the development of any young person, and is a universal right that does not exclude those who are deprived of their liberty. The socio-educational system seeks to provide an inclusive and comprehensive education that takes into account the specific needs of adolescents in conflict with the law and promotes reintegration into society. In this sense, educational and professional training activities represent a significant tool for intervention, allowing young people to acquire skills, knowledge and a new perspective on life and the future. The activities implemented at the Senador Raimundo Parente Socio-Educational Center, such as the use of recyclable materials and cultural projects, have proven effective in expanding the skills of these adolescents and strengthening their confidence in their own abilities.